FINANCIAL CRISES: MEASURES TO MITIGATE THE CONSEQUENCES OF RISKS - Toshpo‘latov Mukhammadsoyib Abdukhakimovich (Web of Journals Publishing, 2025)
Financial crises have a significant impact on the economies of countries and businesses. This article analyzes the main causes of financial risks, their consequences, and measures to mitigate these risks. Methods such as diversification, precautionary planning, and financial monitoring are discussed. The article highlights effective strategies for risk identification and maintaining financial stability.
Keywords: Financial crisis, risk, economic stability, diversification, monitoring.